Dinamika Komunikasi Politik dalam Pemilihan Wali Kota Batu Tahun 2024 - I Made Arie Widyasthana Wartana Putra; Ahmad Luthfi; Jessica Shearen Wijaya Rudijanto; Devi Praggita Maharani (Fakultas Politik Pemerintahan, 2025)
This article examines how political communication developed during the 2024 Batu City Regional Head Election (Pilkada), with an emphasis on the campaign strategy of the candidate pair Krisdayanti (KD) and Kris. To understand how political communication strategies affect the results of the Pilkada, this study uses a literature review approach. This candidate pair used a multi-platform approach to communication, combining conventional media, such as television and newspapers, with digital media, such as Instagram, Twitter, TikTok, and YouTube. In addition, they collaborated with local digital communities and influencers to expand the reach of campaign messages and increase young voter participation. However, despite having the advantage of popularity as public figures, this pair failed to win the Pilkada. The results of the study show that success in local political contestation does not only depend on popularity or aggressive digital strategies, but also requires a holistic approach. This approach includes a balance between traditional and modern strategies, authentic communication, and a deep understanding of the characteristics, needs, and preferences of local communities. This study provides valuable insights into the challenges and success factors in political communication in the Batu City Pilkada, as well as implications for political campaign strategies at the regional level in the future.